Aligning a University English Language Proficiency measurement tool with the CEFR: a case in Malaysia - Baharum, Nurul Najwa; Ismail, Lilliati; Nordin, Nooreen; Razali, Abu Bakar (Universiti Putra Malaysia Press, 2021)
The Common European Framework of Reference (CEFR) describes the capability of learners’ language skills at six reference levels. It is internationally recognised as the standard language proficiency framework for describing language learning, teaching and assessment. Many countries, including Malaysia, have attempted and invested tremendous efforts to adopt the CEFR as a reference for language ability at all levels of education. However, there are many ways of adopting CEFR, and it is a continuous process of alignment between curriculum and assessment. In this regard, this study is carried out to examine how a Malaysian university attempts to demonstrate this alignment by correlating the scores obtained from English language proficiency courses in the university, called the English Language Competence Score Average (ELCSA), to a CEFR-aligned English language proficiency test (Linguaskill). The results showed an overall significant positive correlation that varied in strength. The overall correlation was 0.371, a positive but weak correlation whereby the strongest correlation was seen between ELCSA and CEFR Writing score with a correlation of 0.417, which is positive and moderate in strength. Therefore, it could be identified that a score of 3.25 and 3.5 on the ELCSA can be considered equivalent to a Linguaskill score of 160 (CEFR Band B2). It could be considered that the B2 CEFR level could be subdivided into lower and higher B2. However, there is a need to correlate ELCSA with other CEFR-aligned tests and perform further revisions to the English language proficiency programme at the university to successfully benchmark the programme and its assessment tool, ELCSA, with the CEFR.